The Denser Canopy of Mangrove Drives the Structure of Insect Communities - Yendra Pratama Setyawan; Wakhid; Suhadi (Tropical Life Sciences Research, 2020)
Mangrove restoration in Trenggalek, East Java has resulted an age variation of mangrove ecosystem. Diverse species of insects predominantly found in mangroves were collected using yellow pan traps, swipe nets and by direct picking from three different sites. This research was conducted from April until August 2015. There are 9,181 individual insects associated with mangroves comprised of 42 species from 31 families and eight orders. The first site or the 15 years old mangrove (66.22% canopy cover) indicated the highest Shannon diversity index at 2.54, Evenness index of 0.32 and Margalef richness index of 4.84. The lowest diversity was recorded in the third site or the five years old mangrove (19.65% canopy cover), with the Shannon diversity index at 2.28, Evenness index at 0.26 and Margalef richness index at 4.59. The most abundant species located was the Eristena mangalis, with 1,724 individuals (relative abundance of 18.78%), followed by Monolepta sp. with 1,649 individuals (relative abundance of 17.96%). These are the phytophagous insects associated with mangrove leaves. This study concluded that the older mangrove ecosystem have a denser canopy that supports insect life.